Research Progress on Effects and Treatment of Microplastic Pollution in Freshwater Ecosystems - TANG Hongliang; MA Jinlong; XU Chenchen; PENG Songyao; FENG Lijuan (Renmin Zhujiang)
Microplastics, as a new type of water pollutant, are receiving increasing attention. Due to their widespread distribution, being difficult to degrade, and toxic properties to organisms, they pose a serious threat to the health of freshwater ecosystems. This paper reviews the definition, classification, sources, as well as distribution and migration patterns of microplastics in the freshwater environment. It also discusses the toxicological effects of microplastics on freshwater organisms and the application of physical, chemical, and biotechnological technologies in the removal of microplastics. Microplastics can be categorized into primary and secondary microplastics based on types, sizes, and sources. Comprehensive analysis indicates that selecting appropriate microplastic collection and pretreatment methods is fundamental for quantitative and qualitative analysis and other research. The distribution and migration of microplastics are influenced by factors such as geographical locations, wind, water flow, and flow rate. Studies have shown that microplastics exert toxic effects on the growth and reproduction of freshwater organisms by adsorbing toxic chemicals and microbes on the surfaces, and that microplastics even affect the food chain and the health of freshwater ecosystems. To address these issues, this paper reviews the current applications of physical technologies such as adsorption, membrane filtration and sedimentation, chemical technologies such as coagulation and flocculation processes, oxidation, polymerization and photocatalytic degradation, and biological technologies such as microbial degradation. The paper concludes by proposing research prospects in four aspects: analytical methods for microplastics, environmental toxicity studies, removal technologies, and policies and regulations. This paper aims to provide ideas and references for incorporating microplastic indicators into the health assessment system of rivers and lakes and to offer management strategies for the river and lake health evaluation system.